Trimodal operation of a robust smart organic crystal - Wu, Wenbo (2024)
We describe a dynamic crystalline material that integrates mechanical, thermal, and light modes of operation, with unusual robustness and resilience and a variety of both slow and fast kinematic effects that occur on very different time scales. In the mechanical mode of operation, crystals of this material are amenable to elastic deformation, and they can be reversibly morphed and even closed into a loop, sustaining strains of up to about 2.6%. Upon release of the external force, the crystals resume their original shape without any sign of damage, demonstrating outstanding elasticity. Application of torque results in plastic twisting for several rotations without damage, and the twisted crystal can still be bent elastically. The thermal mode of operation relies on switching the lattice at least several dozen times. The migration of the phase boundaries depends on the crystal habit. It can be precisely controlled by temperature, and it is accompanied by both slow and fast motions, including shear deformation and leaping. Parallel boundaries result in a thermomechanical effect, while non-parallel boundaries result in a thermosalient effect. Finally, the photochemical mode of operation is driven by isomerization and can be thermally reverted. The structure of the crystal can also be switched photochemically, and the generation of a bilayer induces rapid bending upon exposure to ultraviolet light, an effect that further diversifies the mechanical response of the material. The small structural changes, low-energy and weak intramolecular hydrogen bonds, and shear deformation, which could dissipate part of the elastic energy, are considered to be the decisive factors for the conservation of the long-range order and the extraordinary diversity in the response of this, and potentially many other dynamic crystalline materials.